ANALISIS KURIKULUM PENDIDIKAN AGAMA ISLAM BERWAWASAN LINGKUNGAN HIDUP PADA MADRASAH IBTIDAIYAH AL HAFIZIAH MASJURING DESA BONDER KECAMATAN PRAYA BARAT - Fahlawi, Sahrizal; Eliza Pertiwi, Rizka; Sobri, Muhammad (Jurnal El-Hikam, 2024)
This research discusses environmentally friendly Islamic education in Islamic Madrasah Ibtidaiyah Al Hafiziah Desa Bonder Kecamatan Praya Barat. Islamic education covered in the subjects of Al-Quran, Hadith, Aqidah Akhlak, Fiqh, and Islamic Cultural History can be used as a medium to instil environmentally friendly Islamic education in students. This research uses a field research approach and in-depth interviews. The findings of this study show that Islamic education has been integrated in aqidah moral subjects, for example related to animals and plants, while fiqh subjects, such as maintaining body and environmental hygiene. Thus, students have scientific insights that can then be applied to love and protect the environment. Keywords: Kurikulum, Pendidikan Agama Islam, Lingkungan Hidup